Effects of water-salt coordinated regulation technique on ion distribution and antioxidant enzyme activities in tomato - Wang, Weihua; Gong, Yidan; Xing, Xuguang; Zhao, Fengyue; Zhang, Xue (International Journal of Agricultural and Biological Engineering, 2022)
In order to explore the effects of brackish water combined with regulated deficit irrigation of different growth periods, different levels of water, and salt synergistic stress on the characteristics of ion absorption, distribution, transport, and antioxidant enzyme activity of tomatoes, a greenhouse pot experiment was applied. The influencing factors were set as: irrigation water salinity (local shallow groundwater S0 1.1 g/L, S1 2.0 g/L, S2 4.0 g/L), different water deficit levels (W1 70%-80% field capacity (FC), W2 60%-70% FC, W3 50%-60% FC), and three growth stages (T1 seedling stage, T2 blossoming and bearing fruits stage, T3 mature picking stage). Monitoring and analyzing the dynamic changes of K+ and Na+ content in tomato root stems and leaves under water-salt stress and antioxidant enzyme activities of leaves at the seedling stage. The results showed the coordinated regulation of water and salt can significantly change the ion absorption of roots and the transfer between stems and leaves at different growth stages. The roots and leaves of tomatoes mainly accumulated K+, and the stems mainly accumulate Na+. The increase of irrigation salinity can reduce the ratio of K+/Na+ ratio in leaves. Under the coordinated regulation of water and salt, K+ became the main osmotic adjustment ion of the leaves again. The activities of catalase, superoxide dismutase, and peroxidase in tomato leaves increased with the increase of water-salt stress. The results have great significance to the response of crops and to meet the requirements for water quality and quantity of brackish water under water-salt stress at different growth stages of tomatoes. Keywords: brackish water irrigation, water and salinity stress, ion contents, antioxidant enzyme activity DOI: 10.25165/j.ijabe.20221506.6845 Citation: Wang W H, Gong Y D, Xing X G, Zhao F Y, Zhang X. Effects of water-salt coordinated regulation technique on ion distribution and antioxidant enzyme activities in tomato. Int J Agric & Biol Eng, 2022; 15(6): 165–174.